2017
DOI: 10.4007/annals.2017.185.3.7
|View full text |Cite
|
Sign up to set email alerts
|

The sphere packing problem in dimension $8$

Abstract: In this paper we prove that no packing of unit balls in Euclidean space R 8 has density greater than that of the E 8 -lattice packing.We define the density of a packing P as the limit superior ∆ P := lim sup r→∞ ∆ P (r).The number be want to know is the supremum over all possible packing densities ∆ d := sup P⊂R d sphere packing ∆ P , 1 arXiv:1603.04246v2 [math.NT]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
265
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(294 citation statements)
references
References 14 publications
(23 reference statements)
7
265
0
3
Order By: Relevance
“…Example. For d = 8 we can let n = 1 and find that φ(z) = E 2 2 E 2 4 − 2E 2 E 4 E 6 + E 2 6 which matches the function found in [11].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Example. For d = 8 we can let n = 1 and find that φ(z) = E 2 2 E 2 4 − 2E 2 E 4 E 6 + E 2 6 which matches the function found in [11].…”
supporting
confidence: 71%
“…The Schwartz functions constructed by Viazovska, Cohn, Kumar, Miller, Radchenko, and Viazovska, and Cohn and Gonçalves in [11], [5], [6], and [3] showed that there is a surprising and beautiful connection between modular forms and various problems related to sphere packing. It is natural to seek a better understanding of these functions, and to aim for a general framework.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…It has been known for a long time that it is the lattice with the densest sphere packing in R 8 , and the sphere packing with the highest kissing number [38]. Recently, Viazovska showed that it gives the densest sphere packing in R 8 , among all possible packings both lattice and nonlattice [163]. At the time of her work, the densest packing was unknown in R n for all n ≥ 4!…”
Section: What Is E 8 ?mentioning
confidence: 99%
“…The Delsarte LP‐bound has often proved fruitful when dealing with such problems, e.g. in the context of sphere‐packing or in the maximum number of code‐words in error correcting codes . It is based on the observation that the function 1B*1B1 is positive definite on the group G .…”
Section: Introductionmentioning
confidence: 99%